Barriers Factors of Infection Control and Prevention in Intensive Care Units - Mohammadnejad, Esmaeil; Raznahan, Rasool; Ghonoodi, Fatemeh; Waleed Ibraheem, Ali; Ghanei Gheshlagh , Reza; Seifi, Arash (International Journal of Psychosocial Rehabilitation, 2020)
Nosocomial, or hospital-acquired, infections (HAI) are a major problem in ICUs and one of the major causes of hospitalization, medical costs, and mortality. The purpose of this study was to investigate the barrier factors in the prevention and control of nosocomial infections in the intensive care unit. The present study was qualitative research with a conventional content analysis approach. Twenty-one healthcare workers were selected by the purposive sampling method, and a deep and semi-structured interview was conducted with them. Data were analyzed using the qualitative content analysis method. Data analysis revealed the main theme of barrier factors, which included four categories of human factors, environmental factors, individual factors, and complexity. According to the findings, it is necessary to identify facilitators to make nosocomial infections better diagnosed and provide appropriate and effective planning to improve the safety and quality of patient care.